Fat-Phobic and Non-Fat-Phobic Anorexia Nervosa: A Conjoint Analysis on the Importance of Shape and Weight - Korn, Julia; Vocks, Silja; Rollins, Lisa H.; Thomas, Jennifer J.; Hartmann, Andrea S. (Frontiers in Psychology, 2020)
With the introduction of new diagnostic criteria in DSM-5, fear of weight gain no longer represents a sine qua non criterion for the diagnosis of anorexia nervosa (AN). This is of relevance as a subgroup of individuals with AN denies fear of weight gain as the reason for restrictive eating but still remain at a very low weight. As self-reports are susceptible to bias, other methods are needed to confirm the existence of the subtype in order to provide adapted treatment. Therefore, we aimed to measure fear of weight gain using a novel method in clinical psychology, the conjoint analysis (CA). Relative importance and preference scores for various life aspects, including appearance / shape and weight were assessed in women with fat-phobic AN (FP-AN, n = 30), NFP-AN (n = 7), and healthy controls (n = 29). Individuals with FP-AN showed a significant lower preference for weight gain versus weight maintenance than HC (p = .011, partial η2 = .107). Correlation between explicitly assessed drive for thinness and CA score was low. As expected, in FP-AN the explicitly endorsed fear of weight gain was confirmed by the marked preference for weight maintenance compared to HC, while for NFP-AN explicit and implicit measures diverged, indicating that against their self-report they may experience at least some fear of weight gain. The utility of CA as a tool to measure fear of weight gain — and potentially other psychopathological constructs —requires further confirmation.